Resuscitation With Ringer's Lactate Compared With Normal Saline for Pediatric Diabetic Ketoacidosis. Issue 5 (May 2021) - Bergmann, Kelly R.; Abuzzahab, M. Jennifer; Nowak, Jeffrey; Arms, Joe; Cutler, Gretchen; Christensen, Eric; Finch, Mike; Kharbanda, Anupam
Abstract : Objective: The aims of this study were to describe the use of Ringer's lactate (LR) or normal saline (NS) for resuscitation among children with diabetic ketoacidosis (DKA) and compare the effect of fluid type on cost, length of stay, and rate of cerebral edema (CE). Methods: This is a retrospective study of 49, 737 children aged 0 to 17 years with DKA between January 1, 2005, and September 30, 2015, using data from the Pediatric Health Information System. Treatment with LR or NS was identified. Our primary outcomes were total adjusted cost and length of stay. Our secondary outcome was CE rate per 1000 episodes. Results: The majority of patients were treated with NS (n = 43, 841 [88%]) compared with LR (n = 1762 [4%]) or both NS and LR (n = 4134 [8%]). Hospital-year–specific practice patterns were used to investigate the effect of fluid type across resuscitation fluid groups. Total adjusted cost was 1160 less (95% confidence interval, −1468 to −852), or −14.2%, for cases with any episode of LR compared with NS only. Length of stay was not different across groups. The rate of cerebral edema per 1000 episodes was 12.7 for cases with any episode of LR compared with 34.6 NS only (difference, −21.9; 95% confidence interval, −30.4 to −13.3). Conclusions: Ringer's lactate was infrequently used for resuscitation of pediatric DKA patients. However, resuscitation with LR compared with NS was associated with lower total cost and rates of CE. Further investigation using patient-level clinical and laboratory data is needed to evaluate factors that drive cost and risk of CE development with each fluid. Abstract : Supplemental digital content is available in the text.